The Hippo Pathway Effector YAP1 Regulates Intestinal Epithelial Cell Differentiation - Sepideh Fallah; Jean-François Beaulieu (Cells, 2020)
The human intestine is covered by epithelium, which is continuously replaced by new cells provided by stem cells located at the bottom of the glands. The maintenance of intestinal stem cells is supported by a niche which is composed of several signaling proteins including the Hippo pathway effectors YAP1/TAZ. The role of YAP1/TAZ in cell proliferation and regeneration is well documented but their involvement on the differentiation of intestinal epithelial cells is unclear. In the present study, the role of YAP1/TAZ on the differentiation of intestinal epithelial cells was investigated using the HT29 cell line, the only multipotent intestinal cell line available, with a combination of knockdown approaches. The expression of intestinal differentiation cell markers was tested by qPCR, Western blot, indirect immunofluorescence and electron microscopy analyses. The results show that TAZ is not expressed while the abolition of YAP1 expression led to a sharp increase in goblet and absorptive cell differentiation and reduction of some stem cell markers. Further studies using double knockdown experiments revealed that most of these effects resulting from YAP1 abolition are mediated by CDX2, a key intestinal cell transcription factor. In conclusion, our results indicate that YAP1/TAZ negatively regulate the differentiation of intestinal epithelial cells through the inhibition of CDX2 expression.